Understanding Shoppers' Expectations Of Online Grocery Retailing - Reynolds, J; Wilson-Jeanselme, M (Emerald Group Publishing Ltd., 2006)

(untitled)
The purpose of this paper is to analyse the online preference structures of consumers. Novel choice-based conjoint experiments are used and are administered online. A select group of high net worth online grocery shoppers are examined. Both qualitative and quantitative procedures are used to determine the most frequently cited attributes affecting online patronage. Whilst there is no single attribute on which a retailer could develop a competitive edge, a significant market advantage can be gained by being simultaneously "best in class" on the top four attributes. This research approach has significant practical application to a wide range of strategic marketing questions. These findings give focus to the management task facing marketing executives in the UK multichannel grocery market. How these findings might be used within a marketing plan is illustrated.